Prognostic factors in young ovarian cancer patients: An analysis of four prospective phase III intergroup trials of the AGO Study Group, GINECO and NSGO. (October 2016) - Klar, M.; Hasenburg, A.; Hasanov, M.; Hilpert, F.; Meier, W.; Pfisterer, J.; Pujade-Lauraine, E.; Herrstedt, J.; Reuss, A.; du Bois, A.
Abstract: Objectives: We evaluated in a large study meta-database of prospectively randomised phase III trials the prognostic factors for progression-free survival (PFS) and overall survival (OS) in patients < and >40 years of age with advanced epithelial ovarian cancer. Methods: A total of 5055 patients of the AGO, GINECO, NSGO intergroup studies AGO-OVAR 3, 5, 7 and 9 were merged to identify 294 patients <40 years and 4761 patients ≥40 years. We conducted survival analyses and Cox proportional hazard regression models and additionally analysed a very homogeneous subcohort of 405 patients with serous epithelial ovarian cancer, excellent performance status, who had received complete macroscopic upfront cytoreduction and ≥5 chemotherapy cycles. Results: For patients <40 years, the median PFS was 28.9 months and the median OS was 75.3 months, while the median PFS for patients ≥40 years was 18.1 months and the median OS was 45.7 months. Independent prognostic factors were similar in both age groups. In a multivariate analysis including prognostic factors potentially leading to confounding, young age appeared to improve PFS (hazard ratio [HR], 0.86; 95% confidence interval [CI]: 0.72–1.03) and OS (HR, 0.73; 95% CI: 0.59–0.91). The observed effect was even stronger in the subcohort of optimally treated patients with SEOC: PFS (HR, 0.34; 95% CI: 0.19–0.59) and OS (HR, 0.23; 95% CI: 0.09–0.56). Discussion: Prognostic factors were similar in both age groups. Young age appeared a strong independent protective prognostic factor for PFS and OS in the subcohort. Highlights: To detect the effect of young age on survival in ovarian cancer patients. A meta-database analysis of 5055 ovarian cancer patients. Potential confounding and effect measure modification are considered. Prognostic factors of survival are similar in patients under and over 40 years of age. Young age at diagnosis of ovarian cancer improves survival.